A New Pension Formula: For More Fairness and Less Old-Age Poverty - Friedrich Breyer; Stefan Hupfeld (Weekly Report, 2009)
The statutory pension insurance system is set up according to the principle of participatory equivalence. This principle seeks to hold pension claims at a specific ratio to paid contributions so that a redistribution of income does not take place. In truth, however, there is a massive redistribution in favor of wage earners with higher incomes, as these individuals draw on their pensions for a longer period of time due to their greater statistical life expectancy. If life expectancy was taken into consideration in the pension formula, this would not only lead to greater distributional neutrality, it would also lead to significantly less old-age poverty among long-term contributors to the pension system.
Keywords: H55; I38; 330; Social security; Life expectancy; Poverty; Redistribution